(untitled) (IAHS Medical Journal, 2026)
Background: Diabetes Mellitus is one of the most common chronic metabolic disorders affecting millions of people worldwide. Multiple factors appear to be involved in the pathogenesis of Type 2 Diabetes Mellitus (Type 2 DM). One of these factors may be iron overload. Increased serum ferritin concentrations in non-pathologic conditions, reflecting subclinical iron overload, have been reported to be associated with insulin resistance and an increased risk of Type 2 DM. The study aims to evaluate the association of serum ferritin level with type 2 diabetes mellitus patients. Materials and methods: This cross-sectional comparative study was conducted during the period from June 2022 to May 2023 in the Department of Biochemistry at Chittagong Medical College Hospital. The study consists of 110 study population out of which 55 were type 2 diabetic patients and 55 were non- diabetic subjects included by non probability purposive sampling. Fasting Blood Sugar (FBS), Postprandial Blood Sugar (PPBS), HbA1c, serum ferritin and Hb% were calculated following standard protocol. Statistical analysis was performed using SPSS v26.0 statistics. Results: The mean serum ferritin level of the diabetic patients was 146.45 ± 32.11µg/L, significantly higher (p<0.001) than that of the non-diabetic (104.96 ± 22.0 µg/L) group. The mean HbA1c level in the diabetic group was 8.32±1.02 and that in the non-diabetic group was 5.64±0.29. Serum ferritin levels were positively correlated with HbA1c with r =0.59 and p-value <0.001. The correlation of ferritin with duration of diabetes also showed a positive correlation with r =0.39 and p-value < 0.01. Conclusion: The results of this study concluded that there were a strong association and positive correlation between serum ferritin level and poor glycemic status in patients with type 2 diabetes mellitus when compared to non-diabetic individuals. Serum ferritin was also well associated and positively correlated with HbA1c levels. IAHS Medical Journal Vol 8(2), December 2025; 76-79